Dynamics of soliton self-injection locking in optical microresonators - Andrey S. Voloshin (Nature Portfolio, 2021)
Self-injection locking of the pump laser for a soliton microcomb has significantly relaxed the requirements for laser drives. Here the authors study self-injection locking in experiment and theory and reveal that the soliton formation is feasible with detunings unreachable according to previous theories.